Be or not be online engaged: Exploring the flow from stimuli to e-WOM on online retail consumers - Loureiro, S. M. C.; Bilro, R.G. (Exploring the power of electronic word-of-mouth in the services industry, 2020)
Relationship marketing is a field of knowledge that emerged in the 1980s. The relationship between online consumers and brands is embedded in the same relationship marketing paradigm but become a significant issue for companies in the 21st century with the proliferation of Web 2.0. In order to give insights about online engagement and the process behind, this chapter aims (1) to conduct a systematic literature review on online stimuli experience, adaptability, e-WOM, positive/negative emotions, memory, and online engagement; (2) to present a comprehensive framework exposing the flow from stimuli to eWOM on online retail consumers. Findings allow the authors propose online retailer recommendations and suggestions for further research.